2019
DOI: 10.1002/aenm.201901350
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Phase Behavior with Photophysical Properties in Mixed‐Cation Mixed‐Halide Perovskite Thin Films

Abstract: Mixed cation perovskites currently achieve very promising efficiency and operational stability when used as the active semiconductor in thin‐film photovoltaic devices. However, an in‐depth understanding of the structural and photophysical properties that drive this enhanced performance is still lacking. Here the prototypical mixed‐cation mixed‐halide perovskite (FAPbI3)0.85(MAPbBr3)0.15 is explored, and temperature‐dependent X‐ray diffraction measurements that are correlated with steady state and time‐resolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 70 publications
3
24
0
Order By: Relevance
“…As shown in Figure 3 a, a significant blueshift of absorption and a widened bandgap is observed in the p-Si/n-ZnO heterojunction when starting temperature declines [ 113 ]. However, as shown in Figure 3 a,b, for both photoluminescence (PL) spectra and absorption spectra, the (FAPbI 3 ) 0.85 (MAPbBr 3 ) 0.15 perovskite thin films show a red-shift trend [ 39 ]. Thus, a declined optical bandgap at low temperature is calculated.…”
Section: Low-temperature Enhancement In Photoelectric Performancementioning
confidence: 99%
See 4 more Smart Citations
“…As shown in Figure 3 a, a significant blueshift of absorption and a widened bandgap is observed in the p-Si/n-ZnO heterojunction when starting temperature declines [ 113 ]. However, as shown in Figure 3 a,b, for both photoluminescence (PL) spectra and absorption spectra, the (FAPbI 3 ) 0.85 (MAPbBr 3 ) 0.15 perovskite thin films show a red-shift trend [ 39 ]. Thus, a declined optical bandgap at low temperature is calculated.…”
Section: Low-temperature Enhancement In Photoelectric Performancementioning
confidence: 99%
“…There are also investigations focusing on the dynamic theory of phase transition [ 168 , 169 , 170 ], not discussed in detail here. In response to in-depth knowledge of the interplay between low-temperature-caused structure transition and optoelectronic properties, Greenland et al verified the dominated phase of mixed-cation mixed-halide perovskite (FAPbI 3 ) 0.85 (MAPbBr 3 ) 0.1 at different temperatures and observed sudden changes in absorption [ 39 ] and carrier density, as well as the recombination rate at the corresponding phase-transition temperature, shown in Figure 7 c. Lou et al reported the temperature-dependent spectral response of FAPb(Br 0.4 I 0.6 ) 3 . They also reported that β-phase, which possess fewer defects and a narrower band gap, appears at low temperature [ 171 ].…”
Section: Low-temperature Enhancement In Photoelectric Performancementioning
confidence: 99%
See 3 more Smart Citations